Integration of Islamic Science in the Development of Al-Qur’an Studies in Student Final Projects in Indonesia - Hasan, Hamka (Hayula: Indonesian Journal of Multidisciplinary Islamic Studies, 2023)
This study aims to explain the integration of science and Islam contained in the vision and mission of UIN Syarif Hidayatullah Jakarta, Indonesia, as seen in the theme of my student thesis at the Faculty of Science and Technology. This research is qualitative. The object of study for the Faculty of Science and Technology student thesis is the Informatics Systems Study Program at UIN Syarif Hidayatullah Jakarta. Implementation of research in 2000–2020 The instrument used is an observation of the thesis theme, which aims to map the thesis from a scientific integration perspective. Interview techniques and questionnaires for lecturers and students via Google Forms are used to obtain information about obstacles and solutions in student research related to scientific integration. According to the study’s findings, there has been scientific integration in final student assignments in the form of a thesis theme that connects science and the study of the Qur’an with all of its obstacles and challenges. With the concept of policy implementation, it was found that the cause of these obstacles was the vision of scientific integration at the university level, which needed to be entirely appropriately coordinated. The implication is the lack of synchronization between university programs and the units below them. The findings of this study will show a new relationship between religion and science that students can implement in their thesis.